Scenedesmus biomass productivity and nutrient removal from wet market wastewater, a bio-kinetic study - Apandi, Najeeha; Radin Mohamed, Radin Maya Saphira; Al-Gheethi, Adel; Gani, Paran; Ibrahim, Alfituri; Mohd Kassim, Amir Hashim (Springer Nature, 2019)
The current study aims to investigate the production of microalgae biomass as a function for different wet market wastewater ratios (10, 25, 50, 75 and 100%) and Scenedesmus sp. initial concentrations (104 , 105 , 106 , 107 cells/mL) through the phycoremediation process. The biomass production, total nitrogen (TN), total phosphorus (TP) and total organic compounds (TOC) were determined daily. The pseudo-first order kinetic model was used to measure the potential of Scendesmus sp. in removing nutrients while the Verhulst logistic kinetic model was used to study the growth kinetic. The study revealed that the maximum productivity of Scenedesmus sp. biomass was recorded with 106 cells/mL of the initial concentration in 50% wet market wastewater (98.54 mg/L/day), and the highest removal of TP, TN, and TOC was obtained (85, 90 and 65% respectively). Total protein and lipid contents in the biomass yield produced in the wet market wastewater were more than that in the biomass produced in the BBM (41.7 vs. 37.4 and 23.2 vs. 19.2%, respectively). The results of GC–MS confirmed detection of 44 compounds in the biomass from the wet market wastewater compared to four compounds in the BBM. These compounds have several applications in pharmaceutical and personal care products, chemical industry and antimicrobial activity. These findings indicated the applicability of wet market wastewater as a production medium for microalgae biomass.